Edible ginger-derived nanoparticles: A novel therapeutic approach for the prevention and treatment of inflammatory bowel disease and colitis-associated cancer - Zhang, Mingzhen; Viennois, Emilie; Prasad, Meena; Zhang, Yunchen; Wang, Lixin; Zhang, Zhan; Han, Moon Kwon; Xiao, Bo; Xu, Changlong; Srinivasan, Shanthi; Merlin, Didier (Biomaterials, 2016)
There is a clinical need for new, more effective treatments for chronic and debilitating inflammatory bowel disease (IBD), including Crohn's disease and ulcerative colitis. In this study, we characterized a specific population of nanoparticles derived from edible ginger (GDNPs 2) and demonstrated their efficient colon targeting following oral administration. GDNPs 2 had an average size of ∼230 nm and exhibited a negative zeta potential. These nanoparticles contained high levels of lipids, a few proteins, ∼125 microRNAs (miRNAs), and large amounts of ginger bioactive constituents (6-gingerol and 6-shogaol). We also demonstrated that GDNPs 2 were mainly taken up by intestinal epithelial cells (IECs) and macrophages, and were nontoxic. Using different mouse colitis models, we showed that GDNPs 2 reduced acute colitis, enhanced intestinal repair, and prevented chronic colitis and colitis-associated cancer (CAC). 2D-DIGE/MS analyses further identified molecular target candidates of GDNPs 2 involved in these mouse models. Oral administration of GDNPs 2 increased the survival and proliferation of IECs and reduced the pro-inflammatory cytokines (TNF-α, IL-6 and IL-1β), and increased the anti-inflammatory cytokines (IL-10 and IL-22) in colitis models, suggesting that GDNPs 2 has the potential to attenuate damaging factors while promoting the healing effect. In conclusion, GDNPs 2, nanoparticles derived from edible ginger, represent a novel, natural delivery mechanism for improving IBD prevention and treatment with an added benefit of overcoming limitations such as potential toxicity and limited production scale that are common with synthetic nanoparticles.